1989
DOI: 10.1111/j.1151-2916.1989.tb07682.x
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of the Mechanochemically Activated Powders of Hexagonal Boron Nitride

Abstract: Pressureless sintering of hexagonal boron nitride (BN) was performed using a powder activated by mechano‐chemical treatments. Physical properties of the sintered BN bodies depend on the type of starting powder and the conditions of the treatments. The BN body, which was obtained at 2000°C using an appropriate activated powder, was 99 wt% pure and was excellent in mechanical and physical properties, in spite of its low density (1.64 g/cm3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Hagio et al [3,4]. Kurita shows the microstructure of the hBN body without and with Ni, respectively.…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation
“…Hagio et al [3,4]. Kurita shows the microstructure of the hBN body without and with Ni, respectively.…”
Section: Tablementioning
confidence: 97%
“…Thus, hBN has been widely applied as insulators for high-temperature furnaces, protective tubes and insulating sleeves of thermocouples, crucibles, boats and nozzles for molten metals. Pressureless sintering, hot pressing and hot isostatic pressing have been applied for the preparation of hBN [1][2][3][4][5]; however, the densification of hBN is rather difficult due to its strong covalent bonding nature and anistrophic plate-like structure. In the sintering process, a small amount of boron oxide (B 2 O 3 ) has been commonly added to densify hBN powder by liquid sintering [2].…”
Section: Introductionmentioning
confidence: 99%
“…(4) or briquettes furnaces; or, with the heat or use of the What has been said for boride production can also apply to making boron carbide itself, according to equation 3).…”
Section: Powder Production Methodsmentioning
confidence: 99%
“…The usual "aid" is boric oxide, several per cent of which needs to be added to the BN powder (unless it is present already, as in the case of the lower corrunercial grades) to enable it to form a dense machinable ceramic. A very recent paper [4] epitomises the problems by attempting to produce items by the pressure-less sintering of a "mechanochemically activated powder", which is really nothing more than boron nitride powder subjected to excessive and prolonged grinding in air in order to hydrolyse the particle surfaces. All inter-particle bonding when BN is sintered on its own derives from the -B-O-N-boroxole linkages.…”
Section: Fabricationmentioning
confidence: 99%
“…with a nano-size h-BN phase, and the bending strength, fracture toughness of the nano-composites also keep a higher level. [1][2][3][4][5][6][7] In former research, AlN/h-BN composites were fabricated, the mechanical properties, machinability, corrosion behavior and creepage discharze character of composites were investigated, [8][9] the results showed that the AlN/nano h-BN composites had better properties than AlN/micro h-BN composites and monolithic AlN ceramics. The resistance of AlN/h-BN composites is very importance to use this material to be substrate or encapsulation materials, but few reports are about the bulk resistance of nanosized h-BN composites.…”
Section: Introductionmentioning
confidence: 99%